Genetic variation in the PNPLA3 gene and hepatocellular carcinoma in USA: Risk and prognosis prediction. Issue 1 (15th June 2013) - Hassan, Manal M.; Kaseb, Ahmed; Etzel, Carol J.; El‐Serag, Hashem; Spitz, Margaret R.; Chang, Ping; Hale, Katherine S.; Liu, Mei; Rashid, Asif; Shama, Mohamed; Abbruzzese, James L.; Loyer, Evelyne M.; et al.
Abstract Nonalcoholic fatty liver disease (NAFLD) is an emerging epidemic with high prevalence in Western countries. Genome‐wide association studies had reported that a variation in the patatin‐like phospholipase domain containing 3 (PNPLA3) gene is associated with high susceptibility to NAFLD. However, the relationship between this variation and hepatocellular carcinoma (HCC) has not been well established. We investigated the impact of PNPLA3 genetic variation (rs738409: C>G) on HCC risk and prognosis in the United States by conducting a case−control study that included 257 newly diagnosed and pathologically confirmed Caucasian patients with HCC (cases) and 494 healthy controls. Multivariate logistics and Cox regression models were used to control for the confounding effects of HCC risk and prognostic factors. We observed higher risk of HCC for subjects with a homozygous GG genotype than for those with CC or CG genotypes, the adjusted odds ratio (OR) was 3.21 (95% confidence interval [CI], 1.68–6.41). We observed risk modification among individuals with diabetes mellitus (OR = 19.11; 95% CI, 5.13–71.20). The PNPLA3 GG genotype was significantly associated with underlying cirrhosis in HCC patients (OR = 2.48; 95% CI, 1.05–5.87). Moreover, GG allele represents an independent risk factor for death. The adjusted hazard ratio of the GG genotype was 2.11 (95% CI, 1.26–3.52) compared with CC and CG genotypes. PNPLA3 genetic variation (rs738409: C>G) may determine individual susceptibility to HCC development and poor prognosis. Further experimental investigations are necessary for thorough assessment of the hepatocarcinogenic role of PNPLA3. © 2013 Wiley Periodicals, Inc.